Ethical leadership : the quest for character, civility, and community - Fluker, Walter E., 1951- (Prisms., 2009)
"We live in a leadership crisis. "In an age when incompatible worlds collide and when scandals rock formerly stable institutions," says Walter Fluker, "what counts most is ethical leadership and the qualities of personal integrity, spiritual discipline, intellectual openness, and moral anchoring." Fluker finds these characteristics exemplified in the work and thought of black-church giants Martin Luther King Jr. and Howard Thurman." "This volume, for leaders and emergent leaders in religious and other settings, sets forth the context and principles for ethical leadership, particularly for ministries and other professions whose mission directly advances the common good. Fluker's volume grounds leadership in story, the appropriation of one's roots, as a basis for personal and social transformation. He then explores the key values of character, civility, and community for ethical action on the personal, public, and spiritual realms. From these considerations he develops a model of the specific virtues that embody each realm of ethical leadership before applying them to the practical aspects of leadership and decisionmaking"